Äppelpressmassa i Sydsverige - nuvarande användningsområden och möjligheter till nya produkter - Jönsson, Elena (SLU/Horticulture (until 121231), 2010)
Pomace is the solid remains (i.e. stems, pulp, seeds, and skins) after pressing for juice. The annual production of apple pomace is 593 000 ton worldwide. Its field of application depends on local conditions. In order to investigate the field of application of apple pomace in the Southern Sweden, six persons on companies with production of apple juice were interviewed. The area of usage of apple pomace in these six companies was 75% as cattle feed and 25% as feed for wild animals in the forest. Their opinion was that it is no problem to get rid of the apple pomace, but some of them would like to find applications with better profits. One of the ideas is to dry the apple pomace for usage as dry feed for cattle, horses and pets during the whole year around. However, drying apple pomace demands large quantities of energy. An alternative way to feed cattle all the year around would be to store the apple pomace as ensilage. This is a sensitive process that demands correct storage and qualified performance in order to protect the apple pomace as suitable feed for cattle. If it is well processed and mixed with other food the resulting milk can be even of better quality than before, as the SNF-content (SNF=Solid Non Fat) increases. Another possibility to use the apple pomace is to use it as an ingredient in bread baking. Here, the handling of the apple pomace is of great importance in order to achieve a good result. In this master thesis, this was tested by oxidizing the apple component at varying times before baking. The brownish discoloration of white bread is shown and explained. If the apple pomace is added before it is getting brown though, the resulting bread is well tastes. In order to make the process less sensitive to oxidation a possibility would be to bake dark bread instead of white. In dark bread the discolored components are not so obvious. Dark bread with 5-10% additives of apple pomace is juicier and prolongs the feeling of satisfaction. A difficulty with the dark bread compared with the white bread is to make it grow high and achieve the same height as when no apple pomace is added. In conclusion, it can be an interesting option to bake bread with up to 10% of apple pomace due to its nutritive food value and higher content of slow fibers that prolonger the feeling of satiety.